2012
DOI: 10.1097/bpo.0b013e31824b2b1f
|View full text |Cite
|
Sign up to set email alerts
|

Is Bone Mineral Mass Truly Decreased in Teenagers With a First Episode of Forearm Fracture? A Prospective Longitudinal Study

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…Eismann et al [29] demonstrate that during an average time of 15 days, it is also safe a rereduction after redisplacement following initial closed reduction. Cast immobilization should be [33,34]. In conclusion, the analysis of available data in the literature shows that conservative management is a very common, safe and successful treatment option in pediatric forearm fractures (Fig.…”
Section: Complete Fracturesmentioning
confidence: 86%
“…Eismann et al [29] demonstrate that during an average time of 15 days, it is also safe a rereduction after redisplacement following initial closed reduction. Cast immobilization should be [33,34]. In conclusion, the analysis of available data in the literature shows that conservative management is a very common, safe and successful treatment option in pediatric forearm fractures (Fig.…”
Section: Complete Fracturesmentioning
confidence: 86%
“…We focused on the method of treatment with special emphasis on difficulties faced during management and causes of refracture. 8 We studied refracture cases treated both conservatively and surgically. Bould in his study reported 4.9% refractures among 768 children with displaced fractures.…”
Section: Discussionmentioning
confidence: 99%
“…2 The majority of forearm fractures are located in the distal part of the forearm. 8,9 The age distribution of these fractures is bimodal; the peak incidence occurs between ages 10-14, coinciding with the adolescent growth spurt, with a second smaller peak incidence between 5-9 years of age. 9,10 The most common mechanism is a fall (83%) while direct trauma is a distant second (10%).…”
Section: Epidemiologymentioning
confidence: 99%
“…7,9 Loss of reduction is the most common complication in pediatric forearm fractures, with rates between 10 and 60%. 7 Refracture is another rare complication that can happen up to 6 months after the initial injury.…”
Section: Conservative Managementmentioning
confidence: 99%